Caracterização da estrutura organizacional do aglomerado produtivo de Telêmaco Borba - PR - Betim, Leozenir Mendes (2007)
The objective of the present study was to characterize the organizational structure of the lumber productive agglomeration of the city of Telemaco Borba State of Paraná, being as focus the peculiarities of the companies for the fact of being located geographically next to each other. In this direction the following dimensions are analyzed: inter-organizational relationships, multilateral relationship, as well as the economic processes of agglomeration, governing structure and interactive learning. The theoretical references was used for the foundations of the local productive agglomeration, in this research, in the same view the emphasizes of the advantages of the geographical proximity of companies as a form to provide a competitive differential. As to the methodological procedures, the research is classified as descriptive with exploration character. It consists in a quantitative and qualitative research, using a survey. The 62 companies registered in the SINDIMATEL and SINTRACOB, were viewed as the total population, being interviewed 36 companies of the economic segments of lumber, and also interviews with local agents of support to the sector. The main results point out that the Productive Accumulation is characterized as a forming cluster in potential. Even thou there are common characterizes for the companies with productive activities and presence of some characteristics in its productive and organizational system, there are difficulties to be surpassed such as: infrastructure, technological development, development of specialized man power, search for public and private politics that can readjust the sector and make possible its growth, as well as the an awareness on the part of the entrepreneurs in search of class actions.